2000
DOI: 10.1002/1099-0690(200006)2000:12<2265::aid-ejoc2265>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of 1,3-Dipolar Cycloaddition Reactions with Inverse Electron Demand − A DFT Study of the Lewis Acid Catalyst and Solvent Effects in the Reaction of Nitrones with Vinyl Ethers

Abstract: The molecular mechanism for the inverse electron demand 1,3-dipolar cycloaddition of nitrones with vinyl ethers has been characterized using density functional theory methods with the B3LYP functional and the 6−31G* basis set. Relative rates, regioselectivity, endo/exo stereoselectivity, Lewis acid catalyst and solvent effects are analyzed and discussed. Four reactive channels associated with the formation of two pairs of diasteromeric regioisomers have been characterized. Analysis of the geometries of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 44 publications
5
38
0
Order By: Relevance
“…It should be noted that in some previous theoretical studies (49,50) of nitrone cycloadditions with alkenes, it has been suggested that in the reaction the addition of a Lewis acid catalyst changes the mechanism from a classic cycloaddition to a stepwise reaction that is more akin to a Michael addition followed by cyclization. In those studies, the stepwise mechanisms are similar to the stepwise path- ways located in the present case.…”
Section: Lewis Acid Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in some previous theoretical studies (49,50) of nitrone cycloadditions with alkenes, it has been suggested that in the reaction the addition of a Lewis acid catalyst changes the mechanism from a classic cycloaddition to a stepwise reaction that is more akin to a Michael addition followed by cyclization. In those studies, the stepwise mechanisms are similar to the stepwise path- ways located in the present case.…”
Section: Lewis Acid Catalysismentioning
confidence: 99%
“…In general, this class of reactions provides an efficient means of forming heterocyclic components of larger systems, such as that of FR-900482 previously described. 1,3-Dipolar cycloadditions have also been well-studied through computational and theoretical means (19)(20)(21)(22), including those of nitrones with alkenes (23)(24)(25)(26)(27)(28)(29)(30). Such previous work is relevant to the current study since it has been proposed that the strained bonds in the cyclopropane rings exhibit substantial π character (31).…”
Section: Introductionmentioning
confidence: 99%
“…The Lewis acid-catalyzed reaction of nitrone 21 with ethyl vinyl ether 22 (Scheme 8.8) was also investigated for BH 3 and AlMe 3 coordinated to 21 [32]. The presence of BH 3 decreases the activation energy for the formation of 23 by 3.1 and 4.5 kcal mol -1 to 9.6 kcal mol -1 for the exo-selective reaction and 11.6 kcalmol -1 for the endo-selective reaction, respectively, while the activation energy for the formation of 24 increases by > 1.4 kcal mol -1 , compared to those for the uncatalyzed reaction.…”
Section: Normal Electron-demand Reactionsmentioning
confidence: 99%
“…Fig. 8.19 The calculated transition-state structure for the BH 3exo-selective 1,3-dipolar cycloaddition reaction of nitrone 21 with ethyl vinyl ether 22 [32] …”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation